HUMAN RESOURCE MANAGEMENT AND PRACTICES IN SMES IN DEVELOPING COUNTRIES: PRACTICES IN KOSOVO - Ahmeti, Faruk; Marmullaku, Bekim (European Scientific Journal, ESJ, 2015)
The Small and Medium Enterprises (SMEs) are considered as the key contributors in developing countries and plays a significant role in the overall economy in terms of contribution to overall economic development and creation of employment opportunities. The paper will primarily focus on presenting the overview of the human resource practices in SMEs in general, an in specific description in Kosovo SME sector. The economic and politic development in the region, and overall changes in the global market, increases the importance of SMEs in Kosovo’s economy and is seen as unparalleled and crucial to overall Kosovo’s economic development. This paper presents the overview of the HR practices and development in SMEs in Kosovo. As first, this discussed the general views of the SMEs operating in Kosovo, which is the biggest employment sector. The opinions developed supports the argument that SMEs in Kosovo SMEs are yet in the initial stages of developing sustainable and contemporary policies and strategies in developing human capacities, which would result with greeted economic and social development. Some crucial issues concerning to Kosovo’s SMEs are also identified.